Peru Detailed Assessment of Observance : Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank Group (World Bank, Washington, DC, 2018)
The costs of meeting the SDG WASH targets will be several times higher than investment levels during the MDG era (2000–15). The immense scale of the financing gap calls for innovative solutions. In addition to mobilizing more funding another approach is to deliver the needed infrastructure more efficiently and effectively and thus reduce the financing gap. Capital expenditure efficiency (CEE)—the efficient and effective use of capital—is less documented compared to operational efficiency. Although improving operating efficiency is frequently highlighted and readily evaluated, the scope for capital cost efficiencies is poorly understood, frequently overlooked, and difficult to evaluate, even though the scale of savings can be significant—in fact, capital and operating costs are equally important when considering full cost recovery. This study compiles case studies that show the "art of the possible" in CEE. The report is not encyclopedic—many more examples could surface from a comprehensive study. It also doesn't quantify the savings possible through increasing CEE. However, almost all the examples show capital savings of 25 percent or more compared to traditional solutions. This alone this should give policy makers, donors, and utility managers pause for thought and encourage them to develop CEE in their sectors, projects, or utilities. A 25 percent improvement in CEE would allow existing investments to deliver a 33 percent increase in benefits.